Correlation between Depression and Dementia among the Elderly (Jurnal kesehatan komunitas (Journal of community health), 2025)
This study aimed to analyze the relationship between depression and cognitive function among older adults living in a social institution. A quantitative approach with a cross-sectional design was employed. The sample consisted of 68 older adults aged ≥60 years residing at Sentra Terpadu Pangudi Luhur (STPL) in Bekasi City, who were verbally communicative and willing to participate. Depression levels were assessed using the Indonesian version of the Geriatric Depression Scale-15 (GDS-15), while cognitive function was measured using the Indonesian version of the Mini-Mental State Examination (MMSE). Univariate analysis showed that the majority of participants did not experience depression, while half demonstrated cognitive impairment. Bivariate analysis using the Spearman rank correlation test revealed a weak but statistically significant negative relationship between depression and cognitive function. This suggests that higher depressive symptoms tend to be associated with lower cognitive function among older adults. These findings indicate an association between psychological conditions and cognitive decline in institutionalized elderly populations. Although the strength of the association is weak and the study design does not allow for causal conclusions, the results highlight the importance of mental health monitoring in older adults. Further longitudinal studies with larger samples are needed to explore the dynamics of this relationship in greater depth.